A randomized controlled study of a psycho-behavioral intervention combined with a non-benzodiazepine to improve perioperative sleep quality in patients undergoing knee arthroplasty - Jing, Wang; Chunlin, Zhao; Xue, Yang; Tingting, He; Linyan, Yuan; Xiao, Chen; Lingli, Li (Frontiers in Surgery, 2023)
Objective: To clarify the effectiveness and safety of psycho-behavioral intervention combined with a non-benzodiazepine to improve perioperative sleep quality in patients undergoing knee arthroplasty, and also to explore the optimal dosage of non-benzodiazepine (oral zolpidem tartrate) to form a standardized sleep quality management process to promote accelerated recovery of patients. Methods: 240 patients undergoing initial unilateral total knee arthroplasty between January to December 2016 were prospectively included and randomly divided into blank control group (group A), psycho-behavioral intervention group (group B), zolpidem tartrate 10 mg group (group C), and psycho-behavioral intervention + zolpidem tartrate 5 mg group (group D). Sleep, pain, psychological, and knee function scores were compared. Results: There were significant differences between the four groups with respect to Pittsburgh sleep quality index scores, sleep efficiency, Epworth Sleepiness Scale scores, inflammatory indices, pain, and enhanced recovery after surgery indices during hospitalization (P<0.05). Conclusion: Psychological behavioral intervention combined with non-benzodiazepine can improve the perioperative quality of sleep. Compared with drug intervention alone, it reduces the dosage of non-benzodiazepine, alleviates anxiety, improves patient satisfaction, and enhances the quality of life.